1983
DOI: 10.1007/bf00218119
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid-contacting neurons of the central canal and terminal ventricle in various vertebrates

Abstract: Cerebrospinal fluid (CSF)-contacting neurons were studied by means of electron microscopy in the spinal cord and/or terminal ventricle of the ray, Raja clavata (Elasmobranchii), the opossum, Didelphis virginiana (Marsupialia), the mouse, Mus musculus, and the guinea pig, Cavia cobaya (Rodentia). Dendrites of the CSF-contacting neurons in the spinal cord of the ray penetrate the ependyma of the central canal and form terminals bearing stereocilia. Axons apparently belonging to these neuronal perikarya terminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 4 publications
4
33
0
Order By: Relevance
“…Those settled in the lateral wall account for 73±6% of CSF-cNs at P0 (Fig. 1J,K Although spinal CSF-cNs have been described in a wide number of vertebrate species (Vigh and Vigh-Teichmann, 1971;Vigh et al, 1977Vigh et al, , 1983Stoeckel et al, 2003;Marichal et al, 2009;Huang et al, 2006;Djenoune et al, 2014;Jalalvand et al, 2014), their characteristics remain to be fully clarified. We evaluated the expression of distinct cellular markers and found that CSF-cNs express high levels of Nkx6-1 and Sox2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Those settled in the lateral wall account for 73±6% of CSF-cNs at P0 (Fig. 1J,K Although spinal CSF-cNs have been described in a wide number of vertebrate species (Vigh and Vigh-Teichmann, 1971;Vigh et al, 1977Vigh et al, , 1983Stoeckel et al, 2003;Marichal et al, 2009;Huang et al, 2006;Djenoune et al, 2014;Jalalvand et al, 2014), their characteristics remain to be fully clarified. We evaluated the expression of distinct cellular markers and found that CSF-cNs express high levels of Nkx6-1 and Sox2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ependyma is composed of a layer of ciliated mural ependymocytes interspersed with tanycytes and CSF-contacting neurons (Bruni, 1998;Meletis et al, 2008;Sabourin et al, 2009;Marichal et al, 2012). Our genetic-tracing experiments with Gata3 Cre and Gata2 GFP selectively identified spinal CSF-cNs, which exhibit a unique morphology with a prominent dendritic process through the ependymal layer Vigh-Teichmann, 1971, 1998;Vigh et al, 1983) and express Pkd2l1 (Huang et al, 2006;Orts-Del'Immagine et al, 2014, 2016Djenoune et al, 2014).…”
Section: Csf-cns Are Late-born Gata2/3 + Neuronsmentioning
confidence: 86%
See 3 more Smart Citations